2012
DOI: 10.1259/bjr/74797353
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation force impulse quantification: repeatability of measurements in selected liver segments and influence of age, body mass index and liver capsule-to-box distance

Abstract: Objective: To assess the inter-and intra-observer variability of acoustic radiation force impulse (ARFI) quantification in liver segments with influence of age, body mass index (BMI) and liver capsule-to-box (CB) distance. Methods: 10 healthy volunteers were examined twice, by three experienced operators, separated by a 1-week interval. 10 readings were obtained, from segments 3, 5/6 and 7/8. Age, BMI and the CB distance were noted. The Cronbach a statistic for analysis of reliability was performed for the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 22 publications
(18 reference statements)
3
37
1
1
Order By: Relevance
“…The lack of standardized examination protocols and the high reliance on personal physician expertise are expressed in a wide range of measured specificities (73-99 %) and sensitivities (59-94 %), which prevent reliable data acquisition, and therefore preclude comprehensive clinical application [32][33][34][35][36][37]. In concordance with recent studies, we demonstrated good intra-and inter observer reliability for ARFI imaging [38][39][40]. Today, the use of modern ultrasound techniques has proven beneficial for the detection and characterisation of fibrotic parenchymatous lesions in different organs, thus preventing the need for liver biopsy in many cases [15,16,19,20,41].…”
Section: Discussionsupporting
confidence: 82%
“…The lack of standardized examination protocols and the high reliance on personal physician expertise are expressed in a wide range of measured specificities (73-99 %) and sensitivities (59-94 %), which prevent reliable data acquisition, and therefore preclude comprehensive clinical application [32][33][34][35][36][37]. In concordance with recent studies, we demonstrated good intra-and inter observer reliability for ARFI imaging [38][39][40]. Today, the use of modern ultrasound techniques has proven beneficial for the detection and characterisation of fibrotic parenchymatous lesions in different organs, thus preventing the need for liver biopsy in many cases [15,16,19,20,41].…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have reported diagnostic cutoffs for ARFI‐measured liver stiffness for predicting advanced liver fibrosis and, more recently, spleen stiffness for esophageal varices 4 , 21 , 22 . However, standards for use of ARFI have not been established, and there are limited data available concerning the reproducibility of ARFI measurements in the liver 11 , 12 , 22 , 23 and none concerning the reproducibility of ARFI measurements in the spleen among patients under evaluation for chronic liver disease. Moreover, the few studies that did report intraobserver and interobserver variability of ARFI were conducted in countries with much lower prevalence rates of obesity than the United States, where the prevalence rate of obesity is estimated at 35% 23 .…”
Section: Discussionmentioning
confidence: 99%
“…US elastography is more readily available, better accepted by patients, less expensive, and portable (9). However, previous studies showed that potential confounding factors, including age, hepatic steatosis, obesity, and ascites could affect accuracy of US elastography (10)(11)(12)(13)(14).…”
Section: Study Subjectsmentioning
confidence: 99%
“…Previous investigators of US elastography studies who used the acoustic radiation force impulse and the transient elastography techniques suggested that age, steatosis, BMI, and ascites are potential confounding factors for the measurement of liver elasticity (10)(11)(12)(13)(14). Transient elastography, acoustic radiation force impulse, and SWE are all shear wave-based elastography techniques.…”
Section: Study Populationmentioning
confidence: 99%